Can Parental Migration Reduce Petty Corruption in Education? - Höckel, Lisa Sofie; Santos Silva, Manuel; Stöhr, Tobias (Published by Oxford University Press on behalf of the World Bank, 2019)
The income generated from parental migration can increase funds available for children’s education. In countries where informal payments to teachers are common migration could therefore increase petty corruption in education. To test this hypothesis, we investigate the effect of migration on educational inputs. We use an instrumental variables approach on survey data and matched administrative records from the World Bank’s Open Budget Initiative (BOOST) from Moldova, one of the countries with the highest emigration rates. Contrary to the positive income effect, we find that the strongest migration-related response in private education expenditure is a substantial decrease in informal payments to public school teachers. Any positive income effect due to migration must hence be overcompensated by some payment-reducing effects. We discuss a number of potential explanations at the family level, school level or community level. We furthermore rule out several of these explanations and highlight possible interpretations for future research.